Bioremediation of Pulp and Paper Mill Effluent by Newly Isolated Wood Rot Fungi from Western Ghats Area of South India - Selvam, K. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Fifty six samples were collected from Western Ghats area, of Tamilnadu and Karnataka, South India. The collected fungi were isolated and identified based on the key provided previously. Phanerochaete chrysosporium-787 was obtained from Microbial Type Culture Collection, (MTCC) Chandigarh, India and was used as the reference fungus. The fungi were screened for their ligninolytic activity based on their ability to oxidize dyes, poly R-478 and remazol brilliant blue, to degrade native lignin and further confirmation was done by the liberation of ethylene from KTBA (2-keto-4-thiomethyl butyric acid). The color removals in 57 samples were in the range of 11.5 to 38.4% in poly- R dye and 11.1 to 72.0 % in remazol brilliant blue. The mycelial growth rates were in the range of 1.24 to 3.67 mg/day and percent degradation of lignin was found to be in the range 20.4 to 68.8. The ligninolytic activity of the fungi were further confirmed by their ability to release ethylene from KTBA and the results were found to be in the range of 1.210 to 3.121 ppm. From the above screening results three best white rot fungi Polyporus hirsutus, Daedalea flavida, Phellinus sp were selected for bioremediation of pulp and paper mill effluents on laboratory scale and pilot scale. On the laboratory scale a maximum decolourization of 62.2 % was achieved by Phellinus sp on 10th day of treatment. Inorganic chloride 820mg/l (189.7 %,) was liberated by Phellinus sp on the 10th day of treatment. The chemical oxygen demand (COD) was also reduced to 3010 mg/l (42.1%) by Phellinus sp. In pilot scale, a maximum decolourization of 66.2% was achieved by Polyporus hirsutus on 10th day, inorganic chloride 582mg/l (105%) was liberated on the 10th day by Phellinus sp and the chemical oxygen demand (COD) was reduced to 3260mg/l corresponding to 37.3 % by polyporus hirsutus. These results suggest that Polyporus hirsutus and Phellinus sp are efficient for the treatment of pulp and paper industry effluent.